STUDIO KOMIK AGORA DI BANJARABRU - Annada, Katrun; Sarbini, Gusti Novi (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
The Agora Comics Studio in Banjarbaru is a studio building that is not only a place for drawing but also a place that provides a gathering place for the community to enjoy comics with various activities. By applying comic elements into the building as a place to make the story in three dimensions and the people in it are indirectly involved as characters for their own stories. The application of the methods of superimpose theories can solve problems and provide design ideas. Resulting in a 3D Story concept which became the idea of ​​the Agora Comic Study building in Banjarbaru.